PENGARUH HUTAN KEMASYARAKATAN TERHADAP PENDAPATAN RUMAH TANGGA PETANI DI DESA BUKIT TINGGI KABUPATEN LOMBOK BARAT - Herera, Astrit Carolina; Markum; Setiawan, Budhy (Jurusan Kehutanan, 2023)
This study aims to identify the sources of income for farmers' households from within and outside forest areas, analyze the impact of community-based forest management (HKm) on farmers' welfare, and assess the overall welfare levels of farmers' households. The research employed a descriptive method. The sampling area was determined using a purposive sampling technique, while the sample size, comprising 37 respondents, was calculated using the Slovin formula. The distribution of samples was carried out using the Proportional Random Sampling technique, and respondents were selected using a random sampling approach. Data collection methods included literature review, interviews, observations, and questionnaires. The results indicate that farmers' income sources within forest areas derive from managing HKm lands, primarily through the sale of non-timber forest products. Income sources outside the forest include employment as construction workers, traders, laborers, entrepreneurs, shop employees, motorcycle taxi drivers, and rice shop vendors. Income from within forest areas significantly outweighs that from outside forest areas, contributing IDR 32,830,793 (80%) compared to IDR 11,098,163 (20%). Welfare analysis revealed that 24% of respondents fall into the